2018
DOI: 10.1155/2018/4895850
|View full text |Cite
|
Sign up to set email alerts
|

Questions Frequently Asked of Healthcare Professionals: A 2-Year Data Survey Conducted at a Medical Center

Abstract: In this descriptive, retrospective study, we analyzed the types of questions posed by healthcare professionals to drug counselors at a medical center and the types of provision of pharmaceutical advice solicited to improve pharmaceutical care quality and establish clear directions for clinical pharmacist training. We collected 8,558 questions posed by healthcare professionals (physicians, 38%; pharmacists, 39%; nurses, 23%) from the electronic drug information record system from May 2013 to April 2015 in one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
2
4
1
Order By: Relevance
“…This report is consistent with our findings, which may reflect the same setting and level of care of both centers [18]. Another study found that the most frequent need in terms of drug information from HCPs in Hong Kong was related to drug doses and alternative medicine [19]. Alternative medicine is commonly used in Asian countries, reflecting the prevalent use of these remedies in Asian people.…”
Section: Discussionsupporting
confidence: 90%
“…This report is consistent with our findings, which may reflect the same setting and level of care of both centers [18]. Another study found that the most frequent need in terms of drug information from HCPs in Hong Kong was related to drug doses and alternative medicine [19]. Alternative medicine is commonly used in Asian countries, reflecting the prevalent use of these remedies in Asian people.…”
Section: Discussionsupporting
confidence: 90%
“…Although this contradicted the previous findings of Chi-Lien Hou et al, who reported that vancomycin was the single drug most inquired about at a medical center in Taiwan [21], this is not surprising, considering that vancomycin resistance is more prevalent in developed countries [28], whereas Saudi Arabia experiences greater prevalence of clindamycin resistance instead [29,30]. These facts could explain variations in most requested antimicrobial agents while reaffirming that resistance drives the majority of drug information center inquiries.…”
Section: Discussioncontrasting
confidence: 76%
“…About 21% of requests made to the DPIC at Security Forces Hospital, Riyadh, Saudi Arabia, were related to antimicrobial agents, making them the primary reason for contacting DPIC. A previous study analyzing inquiries made to drug information centers from 2013 to 2015 found that questions relating to antimicrobial agents accounted for 20% of questions received [21]. These results validate the importance of healthcare training regarding the use of antimicrobial agents to combat resistance at multiple levels [22].…”
Section: Discussionsupporting
confidence: 62%
“…As drug information experts, pharmacists can help solve this potential problem. Broadly, evidence indicates that when prescribers have an opportunity to collaborate with pharmacists, they pose drug information inquiries (DIIs) [7][8][9][10][11]. Moreover, information-seeking behavior can improve prescribing practices and patient outcomes, such as mortality [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study involved complex inquiries that do not necessarily represent the types of questions that arise during routine practice, and this study's findings may not adequately represent the drug information needs of PCOAs practicing in the United States [9]. Other recent investigations into this subject matter exist but did not analyze DIIs made specifically during the care of older adults [7,8,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%